Short-term magnesium alloy contraceptive ring and preparation method
By using specific ratios of magnesium, zinc and calcium in magnesium alloy birth control rings and using multiple process preparation methods, the existing birth control ring production process and mismatch sizes are solved, and the degradation speed and personalized size matching that meet clinical requirements are achieved, reducing discomfort and pain.
Patent Information
- Application Number
- CN202411830692.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
AI Technical Summary
The production process of existing magnesium alloy birth control rings is complicated, the degradation rate does not meet clinical requirements, and the size does not match the uterine data of female individuals, resulting in discomfort, pain or displacement.
A specific ratio of magnesium, zinc and calcium (30-48% Zn, 0.5-3.0% Ca, balance Mg) is used as elements of the birth control ring, and is prepared by smelting, casting, extrusion and 3D printing processes to ensure that the degradation rate of the birth control ring meets clinical requirements and can be accurately matched according to individual data.
The prepared short-term magnesium alloy birth control ring has the advantages of light weight and degradation speed in accordance with clinical requirements. It is non-toxic to the human body and is nutritious, reducing discomfort and pain caused by size mismatch.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical alloy materials, and in particular relates to a short-term magnesium alloy birth control ring and a preparation method thereof. Background Art
[0002] With the development of society and the improvement of living standards, modern women are paying more and more attention to their own health, their awareness of reproductive health is gradually increasing, and they pay more attention to the safety, effectiveness and long-term effects of contraceptive methods on the body. As a relatively mature contraceptive method, the safety and effectiveness of the IUD have been verified by long-term clinical practice, so it has attracted the attention of many women. The IUDs on the market are generally made of copper-containing and medicated stainless steel, plastic, silicone and other long-term IUDs with stable physical and chemical properties, and the validity period is generally more than 5 years. For people who only take short-term contraception, they will face the trouble of repeatedly taking the IUD. Repeatedly taking the IUD not only increases medical costs but also causes great physical pain and mental stress to patients. In view of this, it is necessary to develop a biocompatible IUD material that can be used for short-term contraception and can be self-degraded, absorbed or detached in the human body environment to reduce the side effects of placing other IUDs or the harm to the body caused by taking contraceptive pills for a long time.
[0003] As a new type of medical device that needs to be implanted in the body, magnesium alloy has received extensive attention from the medical materials community in recent years. Compared with traditional medical metal materials, magnesium alloy as a medical metal material has the following advantages:
[0004] 1. Good biocompatibility, less reaction with human tissue, can reduce inflammation and rejection caused by implants.
[0005] 2. The mechanical properties are suitable and can meet the human body's requirements for the mechanical properties of implant materials.
[0006] 3. After completing its mission, it can degrade by itself and be absorbed by the human body, avoiding the pain and risk of secondary surgery to remove the implant. It also has good processing performance and is inexpensive.
[0007] However, there are still some problems with the existing magnesium alloy materials used as IUDs, such as complicated manufacturing processes, degradation rates that do not meet clinical requirements, or the size of the IUDs produced by existing preparation methods that do not match the uterine data of individual women.
[0008] Therefore, there is an urgent need to provide a short-term magnesium alloy personalized contraceptive ring and a preparation method thereof which has a relatively simple process, meets clinical requirements, and is easy to control in size. Summary of the invention
[0009] In order to make the IUD meet the contraceptive requirements within its validity period and overcome the above-mentioned problems, the present invention proposes a short-term magnesium alloy IUD and a preparation method. The IUD prepared by this method can decompose, fall off or be absorbed by itself in the human body environment outside the validity period. The components of the present invention are reasonably designed, and the degradation rate of the prepared personalized IUD meets clinical requirements, is non-toxic to the human body and is nutritious.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] One of the technical solutions of the present invention:
[0012] A short-term magnesium alloy birth control ring, the element composition of which, in terms of mass percentage, includes:
[0013] 30-48% Zn;
[0014] 0.5-3.0% Ca;
[0015] The balance is Mg;
[0016] Wherein, the zinc element in the short-term magnesium alloy IUD is added as pure zinc as raw material;
[0017] The calcium element is added in the form of Mg-30Ca master alloy (the mass content of calcium element in the master alloy is 30%) as a raw material;
[0018] Magnesium element is added as raw materials in the form of pure magnesium and Mg-30Ca master alloy;
[0019] The purity of pure magnesium and pure zinc is ≥99.9%.
[0020] Beneficial effects: Under the dosage ratio conditions of the above three metal elements defined in the present invention, the prepared contraceptive ring has the advantages of light weight and degradation speed that meets clinical requirements, and is non-toxic to the human body and nutritious; wherein, the magnesium (Mg) defined in the present invention provides basic mechanical properties and biocompatibility, and due to the low electrode potential of magnesium, it is degraded and naturally absorbed in the human body, avoiding the potential risks brought by long-term retention. In addition, magnesium plays a key role in the formation of important compounds required for many metabolic functions of the human body; zinc (Zn) can significantly improve the strength of magnesium alloys and enhance their mechanical properties through the solid solution strengthening mechanism; and can slow down the corrosion rate of magnesium alloys, prolong their service time in the body, and will not cause obvious inflammatory reactions; calcium can refine the grains, further improve the strength and hardness of magnesium alloys, and magnesium, zinc and calcium are one of the main components of bones, which can promote the integration of magnesium alloys with surrounding tissues and improve biocompatibility. That is, through the interaction between the element composition (magnesium, zinc and calcium) of the above dosage ratio defined in the present invention, the clinical needs of different degradation speeds in the short term are met without the need to add other auxiliary components for enhancement.
[0021] Optionally, the contraceptive ring has an elemental composition of 35% Zn, 0.5% Ca, and the remainder Mg, calculated by mass percentage; or
[0022] 38% Zn, 1.0% Ca, balance Mg; or
[0023] 42% Zn, 1.5% Ca, the balance is Mg.
[0024] The second technical solution of the present invention:
[0025] The method for preparing the above-mentioned short-term magnesium alloy IUD comprises the following steps:
[0026] (1) According to the element composition of the short-term magnesium alloy birth control ring, the raw materials are melted and cast in sequence to obtain a cylindrical ingot;
[0027] (2) subjecting the cylindrical ingot to homogenization treatment and then to secondary extrusion to process into a wire;
[0028] (3) The filament is placed in a 3D thixotropic printer for printing to prepare a short-term magnesium alloy IUD.
[0029] Beneficial effects: The present invention sequentially melts, casts, homogenizes and extrude the above raw materials according to their elemental composition, and then uses a high-temperature 3D printer to print out an IUD that matches the corresponding female uterus.
[0030] Optionally, the conditions during the smelting process are: smelting is carried out at 700° C. to 740° C. under a protective atmosphere.
[0031] Optionally, the conditions during the casting process are: casting at 730° C. to 750° C. in an argon atmosphere to obtain a cylindrical ingot.
[0032] Optionally, the two extrusion processes are:
[0033] Performing a first extrusion at 350° C., an extrusion ratio of 16:1, and an extrusion rate of 6.25 m / min to reduce the diameter of the cylindrical ingot from 20 mm to 5 mm;
[0034] Secondary extrusion was carried out at 330° C., an extrusion ratio of 8:1, and an extrusion rate of 6.25 m / min, and the diameter of the cylindrical ingot was extruded from 5 mm to 1.75 mm filaments.
[0035] Optionally, the conditions in the 3D printing process are:
[0036] Printing was performed at a temperature of 420-430°C, a printing speed of 5.0 mm / s, a nozzle diameter of 1.0 mm, and a nozzle-to-substrate distance of 1.0 mm.
[0037] Beneficial effects: The present invention applies 3D thixoforming printing to the three metal raw materials after smelting, so as to accurately print out the IUD that matches the specific data of each woman's uterus, thereby reducing the discomfort, pain or displacement caused by size mismatch.
[0038] Compared with the prior art, the present invention has the following advantages and technical effects:
[0039] The invention improves the strength of the magnesium alloy and reduces the decomposition rate by adding the alloy element Ca, which is useful to the human body, into the magnesium alloy; and controls the degradation time of the birth control ring by adding the element Zn.
[0040] The invention makes full use of the effects of calcium and zinc on the beneficial elements of the human body to meet the nutritional value of magnesium alloy, and can be degraded in the body in a short period of time (8-12 months), and has no toxicity to the human body after degradation. At the same time, the invention has a reasonable composition ratio and is suitable for 3D printing technology. According to the specific data of each woman's uterus, the IUD that matches it can be accurately printed, reducing the discomfort, pain or displacement caused by size mismatch. DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention only describes optional methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] The embodiment of the present invention discloses a short-term magnesium alloy birth control ring, and its element composition, calculated by mass percentage, includes:
[0047] 30-48% Zn;
[0048] 0.5-3.0% Ca;
[0049] The balance is Mg;
[0050] The raw materials of magnesium and zinc are pure magnesium and pure zinc, and the purity of both is greater than or equal to 99.9%.
[0051] As an optional embodiment, the contraceptive ring has the following elemental composition by mass percentage: 35% Zn, 0.5% Ca, and the remainder is Mg.
[0052] As another optional embodiment, the contraceptive ring has the following elemental composition by mass percentage: 38% Zn, 1.0% Ca, and the remainder Mg.
[0053] As another optional embodiment, the contraceptive ring has the following elemental composition by mass percentage: 42% Zn, 1.5% Ca, and the remainder Mg.
[0054] The embodiment of the present invention also provides a method for preparing a short-term magnesium alloy IUD, comprising the following steps:
[0055] According to the mass percentage, the raw materials are sequentially melted, cast, extruded twice and 3D printed to prepare the short-term magnesium alloy IUD.
[0056] In an optional embodiment, the conditions during the smelting process are: smelting is carried out at 700° C. to 740° C. under a protective atmosphere.
[0057] In an optional embodiment, the conditions during the casting process are: casting is performed at 730° C. to 750° C. under an argon atmosphere to obtain a cylindrical ingot.
[0058] In an optional embodiment, the two extrusion processes are:
[0059] Performing a first extrusion at 350° C., an extrusion ratio of 16:1, and an extrusion rate of 6.25 m / min to reduce the diameter of the cylindrical ingot from 20 mm to 5 mm;
[0060] Secondary extrusion was carried out at 330° C., an extrusion ratio of 8:1, and an extrusion rate of 6.25 m / min, and the diameter of the cylindrical ingot was extruded from 5 mm to 1.75 mm filaments.
[0061] In an optional embodiment, the conditions during the 3D printing process are:
[0062] Printing was performed at a temperature of 420-430°C, a printing speed of 5.0 mm / s, a nozzle diameter of 1.0 mm, and a nozzle-to-substrate distance of 1.0 mm.
[0063] The technical solution of the present invention is further illustrated by the following embodiments.
[0064] The raw materials used in the present invention are all purchased from the market.
[0065] The raw materials used in the following examples are pure magnesium, pure zinc and magnesium-calcium master alloy;
[0066] Example 1
[0067] A short-term magnesium alloy birth control ring has the following elemental composition: 35% Zn, 0.5% Ca, and the balance is Mg.
[0068] The preparation method comprises the following steps:
[0069] First, pure magnesium is put into a crucible induction melting furnace. When the melt is heated to about 730°C, pure zinc and Mg-30Ca master alloy are added. During the melting process, argon is used as a protective atmosphere and stirred. When all the metal is melted, it is allowed to stand and argon is introduced for refining. After standing for 20 minutes, the temperature is raised to 740°C under argon protection and cast into a rod (cylindrical ingot) with a diameter of 20 mm. The rod is cooled and subjected to a heat treatment at 400°C for 10 hours. Then, a 200-ton extruder is used to extrude the cylindrical ingot with a diameter of 20 mm at an extrusion ratio of 16:1 at 350°C into a rod with a diameter of 5 mm at an extrusion rate of 6.25 m / min. After that, a 50-ton extruder is used to extrude the rod into a wire with a diameter of 1.75 mm at 330°C, an extrusion ratio of 8:1, and an extrusion rate of 6.25 m / min. The filament was then placed in a 3D thixotropic printer capable of printing at 600°C-700°C, and printed at 430°C, with a printing speed of 5.0mm / s and a nozzle diameter of 1.0mm. The thickness of each layer during the 3D printing process was 0.1mm, the distance from the nozzle to the substrate was 1.0mm, and it was deposited on 1200-grit sandpaper (substrate).
[0070] The magnesium alloy sample is then cleaned with acetone, and then cleaned with anhydrous ethanol and distilled water, blown dry, immersed in a solution containing saturated sodium hydroxide or calcium hydroxide and sodium carbonate, cleaned with distilled water, blown dry, and a degradable nutritional contraceptive ring is obtained.
[0071] Example 2
[0072] A method for preparing a short-term magnesium alloy IUD comprises the following steps:
[0073] Element composition and its weight percentage content: 38% Zn, 1.0% Ca, and the balance is Mg.
[0074] First, pure magnesium is put into a crucible induction melting furnace. When the melt is heated to about 730°C, the remaining metal is added. During the melting process, argon is used as a protective atmosphere and stirred. When all the metal is melted, it is allowed to stand and argon is introduced for refining. After standing for 20 minutes, the temperature is raised to 740°C under argon protection and cast into a rod with a diameter of 20 mm. The rod is cooled and subjected to a heat treatment at 400°C for 10 hours. Then, a 200-ton extruder is used to extrude the cylindrical ingot with a diameter of 20 mm at an extrusion ratio of 16:1 at 350°C into a rod with a diameter of 5 mm at an extrusion rate of 6.25 m / min. After that, a 50-ton extruder is used to extrude the rod into a wire with a diameter of 1.75 mm at 330°C, an extrusion ratio of 8:1, and an extrusion rate of 6.25 m / min. The filament was then placed in a 3D thixotropic printer capable of printing at 600°C-700°C, and printed at 420°C, with a printing speed of 5.0mm / s and a nozzle diameter of 1.0mm. The layer thickness was 0.1mm, the distance from the nozzle to the substrate was 1.0mm, and it was deposited on 1200-grit sandpaper (substrate).
[0075] The magnesium alloy sample is then cleaned with acetone, and then cleaned with anhydrous ethanol and distilled water, blown dry, immersed in a solution containing saturated sodium hydroxide or calcium hydroxide and sodium carbonate, cleaned with distilled water, blown dry, and a degradable nutritional contraceptive ring is obtained.
[0076] Example 3
[0077] A method for preparing a short-term magnesium alloy IUD comprises the following steps:
[0078] Element composition and its weight percentage content: 42% Zn, 1.5% Ca, and the remainder Mg.
[0079] First, pure magnesium is put into a crucible induction melting furnace. When the melt is heated to about 730°C, the remaining metal is added. During the melting process, argon is used as a protective atmosphere and stirred. When all the metal is melted, it is allowed to stand and argon is introduced for refining. After standing for 20 minutes, the temperature is raised to 740°C under argon protection and cast into a rod with a diameter of 20 mm. The rod is cooled and subjected to a heat treatment at 400°C for 10 hours. Then, a 200-ton extruder is used to extrude the cylindrical ingot with a diameter of 20 mm at an extrusion ratio of 16:1 at 350°C into a rod with a diameter of 5 mm at an extrusion rate of 6.25 m / min. After that, a 50-ton extruder is used to extrude the rod into a wire with a diameter of 1.75 mm at 330°C, an extrusion ratio of 8:1, and an extrusion rate of 6.25 m / min. The filament was then placed in a 3D thixotropic printer capable of printing at 600°C-700°C, and printed at 420°C, with a printing speed of 5.0mm / s and a nozzle diameter of 1.0mm. The layer thickness was 0.1mm, the distance from the nozzle to the substrate was 1.0mm, and it was deposited on 1200-grit sandpaper (substrate).
[0080] The magnesium alloy sample is then cleaned with acetone, and then cleaned with anhydrous ethanol and distilled water, blown dry, immersed in a solution containing saturated sodium hydroxide or calcium hydroxide and sodium carbonate, cleaned with distilled water, blown dry, and a degradable nutritional contraceptive ring is obtained.
[0081] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A short-term magnesium alloy IUD, characterized in that: In terms of mass percentage, its elemental composition includes: 30-48% Zn; 0.5-3.0% Ca; The remainder is Mg, and the sum of the weight percentages of each component is 100%.
2. A short-term magnesium alloy IUD according to claim 1, characterized in that: The element composition of the birth control ring is as follows, calculated by mass percentage: 35% Zn, 0.5% Ca, the balance Mg; or 38% Zn, 1.0% Ca, balance Mg; or 42% Zn, 1.5% Ca, the balance is Mg.
3. A method for preparing a short-term magnesium alloy IUD, characterized in that: The following steps are involved: (1) According to the elemental composition of the short-term magnesium alloy IUD according to claim 1 or 2, the raw materials are melted and cast in sequence to obtain a cylindrical ingot; (2) subjecting the cylindrical ingot to homogenization treatment and then to secondary extrusion to process into a wire; (3) The filament is placed in a 3D thixotropic printer for printing to prepare a short-term magnesium alloy IUD.
4. The method for preparing a short-term magnesium alloy IUD according to claim 3, characterized in that: The conditions in the smelting process are as follows: the raw materials of pure magnesium, pure zinc and Mg-30Ca master alloy are mixed, and heated to 700° C. to 740° C. for smelting under a protective atmosphere of argon; Wherein, the purity of the pure magnesium and the pure zinc are both greater than or equal to 99.9%.
5. The method for preparing a short-term magnesium alloy IUD according to claim 3, characterized in that: The conditions in the casting process are: casting is performed at a temperature of 730° C. to 750° C. with argon protection.
6. The method for preparing a short-term magnesium alloy IUD according to claim 3, characterized in that: The two extrusion processes are: The extrusion was carried out once at 350°C, an extrusion ratio of 16:1, and an extrusion rate of 6.25 m / min; The secondary extrusion was carried out at 330°C, an extrusion ratio of 8:1 and an extrusion rate of 6.25 m / min.
7. The method for preparing a short-term magnesium alloy IUD according to claim 3, characterized in that: The conditions in the 3D printing process are: Printing was performed at 420°C-430°C, with a printing speed of 5.0 mm / s, a nozzle diameter of 1.0 mm, and a nozzle-to-substrate distance of 1.0 mm.